2016
DOI: 10.3109/10826084.2016.1152492
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Descriptive Norms on Pregaming Frequency: Tests of Five Moderators

Abstract: Background Pregaming is highly prevalent on college campuses and associated with heightened levels of intoxication and risk of alcohol consequences. However, research examining the correlates of pregaming behavior is limited. Descriptive norms (i.e., perceptions about the prevalence or frequency of a behavior) are reliable and comparatively strong predictors of general drinking behavior, with recent evidence indicating that they are also associated with pregaming. Objectives We tested the hypothesis that hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The reasons for this study's null intervention effects are not entirely clear; yet, it is possible that some student-athletes may not always be able to extrapolate beyond what is directly presented to them in the intervention. As such, myPlaybook could be adapted in such a way that it specifically addresses DG and pregaming behaviors by incorporating social norming (Merrill et al, 2016;Pedersen and LaBrie, 2008) and motivation-matched intervention strategies (e.g., Blevins and Stephens, 2016;Canale et al, 2015;cf. Zamboanga et al, 2018) around these specific behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this study's null intervention effects are not entirely clear; yet, it is possible that some student-athletes may not always be able to extrapolate beyond what is directly presented to them in the intervention. As such, myPlaybook could be adapted in such a way that it specifically addresses DG and pregaming behaviors by incorporating social norming (Merrill et al, 2016;Pedersen and LaBrie, 2008) and motivation-matched intervention strategies (e.g., Blevins and Stephens, 2016;Canale et al, 2015;cf. Zamboanga et al, 2018) around these specific behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Although, not every individual engages in preloading and this must be accounted for in the power analysis. Prior research has found that between 60 -90% of individuals preload before a night-out (Devilly et al, 2019a, b;Hughes et al, 2008;Merrill et al, 2016). Therefore, we aimed to collect a maximum sample size of 700 individuals to ensure our analyses were not underpowered.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately seventy to ninety percent of individuals preload with alcohol before a party, event or night-out (Devilly et al, 2019b;Hughes et al, 2008;Merrill et al, 2016). Preloading is often contextualized as a behaviour practiced by young adults (i.e., 18 -24 years;MacLean & Callinan, 2013;Wells et al, 2015), despite a smaller proportion of adults (i.e., 25 -60 years) also reporting engagement in the practice (de Andrade et al, 2021;Devilly et al, 2017).…”
Section: Introductionmentioning
confidence: 99%